Prevalence and zoonotic potential of canine hookworms in Malaysia - Mahdy Mohammed AK; Lim Yvonne AL; Ngui Romano; Fatimah MR; Choy Seow H; Yap Nan J; Al-Mekhlafi Hesham M; Ibrahim Jamaiah; Surin Johari (Parasites & Vectors, 2012)
Abstract Background Canine hookworm infection is endemic in Southeast Asian countries with a prevalence ranging from 70% to 100%, with zoonotic transmission representing a potentially significant public health concern. However, there are limited data available on the prevalence of canine hookworms in Malaysia. This study was conducted to determine the prevalence of hookworm and Ancylostoma species among dogs in Malaysia. Methods Faecal samples were collected from 221 dogs living in urban areas, rural areas and animal shelters in Selangor. Faecal samples were processed using the formal-ether concentration technique followed by wet mount preparation and iodine staining for the detection of hookworm eggs. Samples positive for hookworm eggs were examined using PCR, targeting ITS2 and 28 s rRNA region, and subsequently sequenced in both directions. The sequences were phylogenetically analysed using MrBayes for Bayesian Inference. Results The overall prevalence of hookworm among dogs was 48% (95%CI; 41.41–54.95). Rural stray dogs had the highest prevalence 71.4% (95%CI; 61.13–81.49) followed by urban stray dogs, recording 48% (95%CI; 34.15–61.85) and lastly dogs in shelters with 28.7% (95%CI; 19.56–37.84). Logistic regression identified rural stray dogs as a high risk group (OR = 4.55, 95%; 2.50–8.31) and keeping dogs in shelters as a protective factor (OR = 0.24, 95%; 0.14–0.43). Molecular methods identified both Ancylostoma ceylanicum and Ancylostoma caninum with A. ceylanicum being predominant among urban stray dogs. Rural dogs had a higher prevalence of A. caninum than A. ceylanicum, while both species showed equal distribution among dogs in shelters. Phylogenetic analysis placed A. ceylanicum isolated from dogs in one group with A. ceylanicum human isolates. Conclusion This study indicates that dogs have the potential to act as reservoir hosts of human hookworm infection in Malaysia. This finding necessitates the inclusion of dogs in any interventions to combat hookworm in the country.